2021
DOI: 10.1111/myc.13361
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution inflammatory syndrome in non‐HIV cryptococcal meningitis: Cross‐talk between pathogen and host

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For immunocompetent individuals, pathogenic cytokine release mediated by PANoptosis through membrane pores and cell lysis could drive lifethreatening damage to host tissues and organs and lead to adverse clinical outcomes (30). MCP-1 was reported to be correlated with CM-associated immune reconstitution inflammatory syndrome (IRIS) in HIV-negative populations (31). In our present study, we demonstrated the diversity of immune mechanisms with higher scores for PC-1 associated with disease severity, suggesting that a combined inflammatory response involving multiple immune mediators may be critical to disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For immunocompetent individuals, pathogenic cytokine release mediated by PANoptosis through membrane pores and cell lysis could drive lifethreatening damage to host tissues and organs and lead to adverse clinical outcomes (30). MCP-1 was reported to be correlated with CM-associated immune reconstitution inflammatory syndrome (IRIS) in HIV-negative populations (31). In our present study, we demonstrated the diversity of immune mechanisms with higher scores for PC-1 associated with disease severity, suggesting that a combined inflammatory response involving multiple immune mediators may be critical to disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have mainly involved subjects with HIV and CM coinfection in a high HIV burden setting due to increased susceptibility to CM in HIV patients (11). In addition, previous work has also shown that population heterogeneity affects the immune response to the pathogen, resulting in altered clinical symptoms and prognoses (12,13). Recently, a novel predictive model was established for calculating one-year mortality in CM (14).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cryptococcal PIIRS in HIV-negative CM patients is also an immune reconstitution resulting from an interaction between Cryptococcus and host factors. Cryptococcus infection had a local immune suppression effect, which may lead to a subsequent partial immune reconstitution after effective antifungal treatment [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%